Executive Director’s Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2013)
People in every organization talk about “building the team”, “working as a team”, and “my team” but few understand how to create the experience of teamwork or how to develop an effective team. Belonging to a team involves feeling part of something larger than yourself and it has a lot to do with having an understanding of the mission or objectives of your organization.